Analisa Laporan Keuangan sebagai Alat untuk Menilai Kinerja pada KSU “Kencana Makmur” Cabang Laren - Firman Nur Aprilianto; Biyati Ahwarumi; Anisatul Mahmudah (Al-Muzdahir : Jurnal Ekonomi Syariah, 2019)
KSU Kencana Makmur Laren Branch needs to analyze financial statements in order to know the company's financial picture from period to period. Qualitative research. The research formulation consists of: 1) How is the financial reporting system at KSU "Kencana Makmur" Laren Branch?, and 2) How is the use of financial statements to analyze financial ratios in measuring the level of Liquidity, Solvency, and Profitability at KSU "Kencana Makmur" Branch Laren?. The method used in this research is descriptive analysis research method, with data collection procedures, interviews, and documentation. From this research, the results obtained are that: 1) The financial reporting system of KSU Kencana Makmur Laren Branch follows the application of the sharia cooperative version of the banking system data base, where every data transaction is recorded in the existing data application. 2) The financial performance of KSU Kencana Makmur Laren Branch in 2012 to 2014 increased and decreased as follows: Liquidity: (a). Current Ratio is 2.46% (in 2012), 2.29% (in 2013), and 2.59% (2014). (b). The Quick Ratio was 2.4% (in 2012), 2.3% (in 2013) and 2.5% (in 2014). Solvency: (a). The Total Debt to Total Asset Ratio was 0.5% (in 2012), 0.6% (in 2013) and 0.6% (in 2014). Profitability: (a). Net Profit Margin, by 0.2%% (in 2012), by 0.6% (in 2013) and by 0.4% (in 2014). (b). Return on Equity Capital was 0.1% (in 2012), 0.2% (in 2013) and 0.2% (in 2014). It can be concluded that the financial condition of KSU Kencana Makmur Laren Branch in 2012 to 2012 was not in a good condition, especially the level of profit.